2015
DOI: 10.1002/pmic.201400454
|View full text |Cite
|
Sign up to set email alerts
|

Unrestricted modification search reveals lysine methylation as major modification induced by tissue formalin fixation and paraffin embedding

Abstract: Formalin-fixed paraffin-embedded (FFPE) tissue is considered as an appropriate alternative to frozen/fresh tissue for proteomic analysis. Here we study formalin-induced alternations on a proteome-wide level. We compared LC-MS/MS data of FFPE and frozen human kidney tissues by two methods. First, clustering analysis revealed that the biological variation is higher than the variation introduced by the two sample processing techniques and clusters formed in accordance with the biological tissue origin and not wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 37 publications
8
43
0
Order By: Relevance
“…Researchers have avoided using FFPE tissue for proteomics in the past because of concerns that the protein crosslinks generated during FFPE processing will prevent the detection of proteins using mass spectrometry or lead to inferior results compared to those using frozen, unfixed tissue. However, we (and an increasing number of other researchers, primarily in the cancer field) have shown that this is not the case [26]. The method described below has been specifically optimized to use FFPE tissue because the abundance of human FFPE tissue specimens is a potential gold mine for future studies of human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have avoided using FFPE tissue for proteomics in the past because of concerns that the protein crosslinks generated during FFPE processing will prevent the detection of proteins using mass spectrometry or lead to inferior results compared to those using frozen, unfixed tissue. However, we (and an increasing number of other researchers, primarily in the cancer field) have shown that this is not the case [26]. The method described below has been specifically optimized to use FFPE tissue because the abundance of human FFPE tissue specimens is a potential gold mine for future studies of human disease.…”
Section: Introductionmentioning
confidence: 99%
“…As PTM analyses are often based on single peptide identifications, they are more error-prone than protein studies. To identify potential sources of wrongly assigned PTMs in kidney disease proteomics, formalin-induced alterations in FFPE samples compared with freshly frozen samples of human kidney tissue have been characterized in a label-free proteomic approach (Zhang et al 2015). In an open modification search, the authors found +12, +14, +16, +30 and +58 Da mass shifts on various amino acid residues of peptides isolated from FFPE samples, shifts that were not present in freshly frozen samples.…”
Section: Quantitative Ms-based Proteomicsmentioning
confidence: 99%
“…Luckily, the overall number of peptides containing a formalin-induced methylation was in an acceptable low range (2-6%). However, since methylations on histone lysines often play a crucial role in the regulation of gene expression and chromatin remodeling, this formalininduced artifact should be taken into account when studying methylation events in renal FFPE specimens (Zhang et al 2015).…”
Section: Quantitative Ms-based Proteomicsmentioning
confidence: 99%
“…This can be accomplished using two bioinformatics approaches. The more general approach uses an unrestricted modification search to extract the modifications in the sample directly from the MS/ MS data without the need for prior configuration [16]. Using this method, unexpected modifications are detected in an unbiased manner.…”
Section: Bioinformatics Analysis Of Ffpe Proteomic Datamentioning
confidence: 99%
“…It is likely that formaldehyde-induced protein adducts undergo further reactions during histological processing. Using an unrestricted modification search method, Zhang et al [16] identified the presence of methylated lysine in FFPE proteomes: a reaction not seen in aqueous solutions of protein and formaldehyde. Ethoxymethylation of the primary amine is observed in 2′-deoxyadenosine 5′-monophosphate when the nucleotide is transferred to ethanol after reaction with formaldehyde in aqueous solution [18].…”
Section: Bioinformatics Analysis Of Ffpe Proteomic Datamentioning
confidence: 99%